Comparative growth and survival performance of sea cucumber (Holothuria scabra) in co-cultured pen system with commercial macroalgae - Muumin I. Hamad*, Augustine W. Mwandya, Renalda S. Munubi, Sebastian Chenyambuga and Heiromin A. Lamtane. (African Journal of Biological Sciences, 2019)
Mariculture has recently been adopted in many parts of coastal East Africa as a source of income and employment to many women and heartbroken fishermen who are the main victim of dwindling wild stock of aquatic resources. The sea cucumber (Holothuria scabra) has for long time been collected and sold as export marine product. Macroalgae (Eucheuma denticulatum and Kappaphycus alvarezii) are the common cultured seaweed species that provide hope for future increase in mariculture production. An experiment was conducted along the intertidal lagoon of Unguja Ukuu village in Zanzibar to assess the survival and growth performance of sea cucumber (H. scabra) in two separate pens under co-cultured systems with E. denticulatum and K. alvarezii. Juvenile sea cucumber H. scabra with mean weight (± se) of 67.18 ± 2.06 were integrated with the two common commercial seaweed in pen system for 10 weeks. The results revealed that the growth rate and survival of H. scabra, E. denticulatum and K. alvarezii were better under integration system. The growth of H. scabra was higher (1.038 gd-1) in pen systems co-cultured with K. alvarezii compared to 0.898 gd-1 in pen systems co-culture with E. denticulatum. Survival rate of H. scabra was higher (76%) in the pen systems co-cultured with E. denticulatum compared to that (70%) observed in pen systems co-cultured with K. alvarezii. The results suggest that the best integration of sea cucumber and macroalgae is between H. scabra and K. alvarezii. However, reliable source of H. scabra juvenile is essential for the future expansion of pen co-culture system.
Keywords: Mariculture, Seacucumber, Macroalgae, Co-culture